2014
DOI: 10.4236/ajps.2014.58120
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of Diuron in Soil Environment: Influence of Cyanobacterial Mat

Abstract: Diuron is a herbicide widely used in the Middle East; its field application creates many environmental problems. This study investigated the bioremediation of Diuron in soil environment by Cyanobacterial mats collected from Gaza Wadi. Various concentrations of Diuron were injected in water saturated soil samples pre-treated with Cyanobacterial mat for several periods. Percent growth of Jews mallow as a test plant was taken as indicator of biodegradation of Diuron. Results showed that Diuron was degraded in soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 20 publications
6
21
0
Order By: Relevance
“…The data in Table 2 indicate strong positive correlation. These data agree with Safi et al [30] who found that Molokhia was sensitive to diuron.…”
Section: Bioassay Studiessupporting
confidence: 93%
“…The data in Table 2 indicate strong positive correlation. These data agree with Safi et al [30] who found that Molokhia was sensitive to diuron.…”
Section: Bioassay Studiessupporting
confidence: 93%
“…The explanation of these results is that cyanobacterial mats degrade Malathion molecules to non-toxic fragments and use them as a source of energy. These results agree [4,5], which reported the derivative ability of cyanobacterial mats for Acetochlor and Diuron. Further support to our results is in Singh et al [29] report that stated higher levels of Malathion degradation in soil due to a mixed culture of three bacterial strains.…”
Section: Effects On Population Growthsupporting
confidence: 91%
“…Bromacil may inhibit photo system I and/or II and thus reduce population growth. Moreover, it can be hypothesized that at low applied concentrations, cyanobacterial mats may undergo fast adaptation and use the herbicide as a source of energy [5] or undergo community changes [3]. Furthermore, cyanobacterial mats may contain sensitive, tolerant and/or resistant species.…”
Section: Effects Of Chemical Mixturesmentioning
confidence: 99%
See 1 more Smart Citation
“…The bioactivity of Nemacur was tested against fish larvae, have 5 ± 0.5 g body weight each according to previous report [33] …”
Section: Nemacur Bio-activity Testmentioning
confidence: 99%